2022
DOI: 10.1126/science.abo2401
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids and glucose prime late-stage fungal biotrophy in maize

Abstract: Many plant-associated fungi are obligate biotrophs that depend on living hosts to proliferate. However, little is known about the molecular basis of the biotrophic lifestyle, despite the impact of fungi on the environment and food security. In this work, we show that combinations of organic acids and glucose trigger phenotypes that are associated with the late stage of biotrophy for the maize pathogen Ustilago maydis . These phenotypes include the expression of a set of effectors normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Of note, a similar hypothesis has been recently proposed for another U. maydis b-1,3 glucanase (Erc1) whose activity toward laminarihexaose has been shown to suppress laminarihexaoseinduced ROS burst in plant leaves (35). All in all, it is clear that the fate and role of FCW/PCW-derived oxidized products released by fungal oxidative enzymes is an emerging matter of utmost importance (38,(44)(45)(46)(47). Conclusions.…”
Section: Discussionsupporting
confidence: 66%
“…Of note, a similar hypothesis has been recently proposed for another U. maydis b-1,3 glucanase (Erc1) whose activity toward laminarihexaose has been shown to suppress laminarihexaoseinduced ROS burst in plant leaves (35). All in all, it is clear that the fate and role of FCW/PCW-derived oxidized products released by fungal oxidative enzymes is an emerging matter of utmost importance (38,(44)(45)(46)(47). Conclusions.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, there is increasing evidence that Grx4 is also connected to oxygen sensing and regulation via sterol binding transcription factors such as SrbA and the transcription factor AtrR in A. fumigatus [35]. In U. maydis, we previously showed that cultures with the combination of glucose and malate form melanin and are hypoxic, and we determined that tumor tissues in leaves and stems during biotrophy are also reduced in oxygen levels [5]. It is tempting to speculate that oxygen sensing via an unknow transcription factor together with Grx4/Urbs1 regulates iron homeostasis, mitochondrial functions (electron transport and the TCA cycle), ergosterol synthesis, and heme-related functions, and integrates central metabolism with the mating pathway to influence virulence and biotrophy.…”
Section: Discussionmentioning
confidence: 91%
“…The salt solution was prepared without FeCl 3 . All other components of the low iron MM are identical to regular MM [1,5]. Glucose and arabinose were used at 1%.…”
Section: Low Iron Minimal Medium (Mm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria play a central role in respiratory metabolism for fungal pathogens of plants and animals, and support the ability of fungi to sense environmental and host conditions (1)(2)(3)(4)(5). The importance of mitochondrial functions in pathogenesis has been demonstrated for a number of fungal pathogens of humans including Cryptococcus neoformans and the related species C. gattii (1,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%